A Dijkstra’s Mobile Web Application Engine for Generating Integrated Light Rail Transit Route - Haziq Lim, AM; Wan Sazli, NS; Hussin, B.; Azlianor, A. A.; Suhaizan, SM; Massila, K (World Scientific and Engineering Academy and Society (WSEAS), 2010)
In the capital city of Malaysia, Integrated Light Rail Transit (LRT) System is one of the most importance public transportation as it connects some key districts to historical, interesting places, business areas and shopping malls are concentrated. The train services are running independently but have interchanges to integrate from one different LRT lines to the others. These interchanges could cause traveler a troublesome when they are choosing incorrect destination station especially on different LRT lines which contribute to time consuming and high costing. In previous research we are implemented the mobile web application using rules based algorithm where the destination-oriented routes need to be dynamically generated by determining the nearest station according to the specific places. Currently, our research is focusing on Dijkstra’s algorithms to provide more effective and intelligent shortest path system to provide the solution for traveler to reach the desired destination. In this paper, we discuss the results from our Dijkstra’s application prototype.